Ultra-broadband photon harvesting in large-area few-layer MoS2 nanostripe gratings. Issue 48 (15th December 2020) - Bhatnagar, Mukul; Giordano, Maria Caterina; Mennucci, Carlo; Chowdhury, Debasree; Mazzanti, Andrea; Della Valle, Giuseppe; Martella, Christian; Tummala, Pinakapani; Lamperti, Alessio; Molle, Alessandro; Buatier de Mongeot, Francesco
Abstract : Flat optics photon harvesting, based on cm-scale MoS2 nanostripe arrays, induces an ultra-broadband enhancement (≈400%) of optical absorption. Abstract : Flat optics nanoarrays based on few-layer MoS2 are homogeneously fabricated over large-area (cm 2 ) transparent templates, demonstrating effective tailoring of the photon absorption in two-dimensional (2D) transition-metal dichalcogenide (TMD) layers. The subwavelength subtractive re-shaping of the few-layer MoS2 film into a one-dimensional (1D) nanostripe array results in a pronounced photonic anomaly, tunable in a broadband spectral range by simply changing the illumination conditions (or the lattice periodicity). This scheme promotes efficient coupling of light to the 2D TMD layers via resonant interaction between the MoS2 excitons and the photonic lattice, with subsequent enhancement of absorption exceeding 400% relative to the flat layer. In parallel, an ultra-broadband absorption amplification in the whole visible spectrum is achieved, thanks to the non-resonant excitation of substrate guided modes promoted by MoS2 nanoarrays. These results highlight the potential of nanoscale re-shaped 2D TMD layers for large-area photon harvesting in layered nanophotonics, quantum technologies and new-generation photovoltaics.